북미 천연가스 현물시장간의 가격발견과 동태적 상호의존성에 대한 연구 - 박해선; Hae Sun Park (자원·환경경제연구, 2006)
Combining recent advances in causal flows with time series analysis, relationships among eight North American natural gas spot market prices are examined. Results indicate that price discovery tends to occur in excess demand regions and move to excess supply regions. Across North America, the U.S. Midwest region represented by Chicago spot market is the most important market for price discovery. The Ellisburg-Leidy Hub in Pennsylvania is important in price discovery, especially for markets in the eastern two-thirds of the U.S. Malin Hub in Oregon is important for the western markets including the AECO Hub in Alberta, Canada. 본 연구에서는 시계열분석기법과 그래프 이론을 활용하여 8개의 북미천연가스 현물시장간의 관계를 분석하였다. 벡터오차수정모형과 탐욕동급검색 알고리즘(Greedy Equivalence Search Algorithm)을 활용한 그래프 이론을 통해 시장간의 관계를 분석한 결과, 가격발견과정은 초과수요지역에서 발생하여 초과공급지역으로 진행되는 것으로 나타났다. 북미 천연가스 현물시장 중에서 시카고로 대표되는 미국의 중서부지역이 가격발견과정에 있어 가장 중요한 시장인 것으로 나타났으며 미국 동부지역에 있어 펜실바니아의 Ellisburg-Leidy Hub이, 그리고 미국서부지역에 있어서는 Malin Hub이 가격발견과정에 있어 중요한 시장인 것으로 나타났다.